Dietary supplementation of honey bee larvae with arginine and abscisic acid enhances nitric oxide and granulocyte immune responses after trauma - Negri, Pedro (2017)
Many biotic and abiotic stressors impact bees’ health, acting as immunosupressors and contribute to colony losses. Thus, the importance of studying the immune response of honey bees is central to develop new strategies aiming to enhance bees’ fitness to confront the threats affecting them. If a pathogen breaches the physical and chemical barriers, honey bees can protect themselves from infection with cellular and humoral immune responses which represent a second line of defense. Through a series of correlative studies we have previously reported that abscisic acid (ABA) and nitric oxide (NO) share roles in the same immune defenses of Apis mellifera (A. mellifera). Here we show results supporting that the supplementation of bee larvae’s diet reared in vitro with L-Arginine (precursor of NO) or ABA enhanced the immune activation of the granulocytes in response to wounding and lipopolysaccharide (LPS) injection.